Snowie Rolie - Joyce, William ([New York] : Laura Geringer Books, 2000)
When the sun begins to melt the snow, Olie and Zowie take their snowman friend, Mr. Snowie, to a new home in Chillsville.
Publisher's Weekly
Booklist
Kirkus Review
2.4
K-3
Keywords: Snowmen -- Fiction; Snow -- Fiction; Snowmen -- Fiction; Snow -- Fiction